2017
DOI: 10.1016/j.celrep.2017.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasomes Control the Homeostasis of Medullary Thymic Epithelial Cells by Alleviating Proteotoxic Stress

Abstract: The sole nonredundant role of the thymic medulla is to induce central tolerance, a vital process that depends on promiscuous gene expression (pGE), a unique feature of medullary thymic epithelial cells (mTECs). Although pGE enhances transcription of >3,000 genes in mTECs, its impact on the regulation of protein homeostasis remains unexplored. Here, we report that, because of pGE, mature mTECs synthesize substantially more proteins than other cell types and are exquisitely sensitive to loss of immunoproteasomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…In this context acini and macrophages were affected, considering that IL-1β is exclusively expressed by macrophages (14). Besides the differences detected in cytokine production, we also observed that immunoproteasome deficiency (55)(56). In our work, we show that the immunoproteasome is crucial for limiting UPR activation in isolated pancreatic acini.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this context acini and macrophages were affected, considering that IL-1β is exclusively expressed by macrophages (14). Besides the differences detected in cytokine production, we also observed that immunoproteasome deficiency (55)(56). In our work, we show that the immunoproteasome is crucial for limiting UPR activation in isolated pancreatic acini.…”
Section: Discussionsupporting
confidence: 61%
“…The UPR restores ER protein homeostasis through inhibition of protein synthesis, enhancement of protein folding and degradation mechanisms, such as autophagy and the UPS (20). Recently, the UPR and the immunoproteasome have appeared as pivotal networks in the maintenance of protein homeostasis and cell fate control (5556). In our work, we show that the immunoproteasome is crucial for limiting UPR activation in isolated pancreatic acini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of HSP70 chaperones increases in response to various stressful stimuli, especially those causing oxidative stress or endoplasmic reticulum stress (40). We did not find signs of endoplasmic reticulum stress in the DEG dataset according to biomarker gene expression (41). However, thymocytes from Psmb11 2 /2 mice showed upregulation of several oxidantinduced transcripts, namely Fos, Jun, Hsph1, Hspa1a, Hspa1b, Gadd45, and Hmox1 (heme oxygenase) (42) (Fig.…”
Section: Lack Of Thymoproteasomes Induces Oxidative Stress In Sp Thymmentioning
confidence: 98%
“…Moreover, iPs facilitate degradation of oxidized proteins and maintain cellular homeostasis during stress ( Pickering et al., 2010 ; Yun et al., 2016 ). Recent study by St-Pierre and coauthors highlight the role of Ips in adaptation of medullary thymic epithelial cells characterized by high levels of protein synthesis to proteotoxic stress ( St-Pierre et al., 2017 ). In addition, iPs were proposed to be involved in production of peptides which participate in cell-cell interactions in order to maintain nervous system plasticity in mice lacking β2-microglobulin ( Lyupina et al., 2013 ).…”
Section: Main Textmentioning
confidence: 99%